2015
DOI: 10.1007/s00468-015-1161-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid root elongation by phreatophyte seedlings does not imply tolerance of water table decline

Abstract: Key message Despite high rates of root elongation during phreatophyte establishment, once connection to groundwater has occurred and leaf area develops, seedlings demonstrate limited capacity for root elongation in response to groundwater decline. Abstract In a water-limited environment, rapid root elongation immediately after germination can be critical for a plant to reach deeper water sources such as a water table to avoid water deficit stress. However, once plants have accessed a water table, their continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…On the other hand, the proportion of live fine-roots in the 0-20 cm soil layer in the present study increased in summer or rainy season (Figure 1b), when the soil moisture content was higher due to high rainfall ( Figure 2). The dependence of fine-root production on the soil water content and fertility has previously been reported by Canham et al (2015), who found higher levels of fine-root production in soil with higher moisture content and fertility. Similarly, Nguyen et al (2019) observed higher levels of fine-root production in a plantation during rainy season compared with dry season and in a fertilisation treatment compared with a non-fertilisation treatment and concluded that this was due to the greater ability of larger numbers of fine-roots to absorb nutrients and water efficiently.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, the proportion of live fine-roots in the 0-20 cm soil layer in the present study increased in summer or rainy season (Figure 1b), when the soil moisture content was higher due to high rainfall ( Figure 2). The dependence of fine-root production on the soil water content and fertility has previously been reported by Canham et al (2015), who found higher levels of fine-root production in soil with higher moisture content and fertility. Similarly, Nguyen et al (2019) observed higher levels of fine-root production in a plantation during rainy season compared with dry season and in a fertilisation treatment compared with a non-fertilisation treatment and concluded that this was due to the greater ability of larger numbers of fine-roots to absorb nutrients and water efficiently.…”
Section: Discussionsupporting
confidence: 63%
“…E. grandis trees are better adapted to the cold climate in winter at our study site than A. mangium trees, which could account for the higher fine-root production in the topsoil in E. grandis monoculture and mixed-species stands than in A. mangium monoculture. A strong influence of exogenous factors such as soil temperature and water content (Canham et al 2015), as well as endogenous factors such as photosynthate availability, on fine-root phenology is well documented (McCormack et al 2015).…”
Section: Fine-root Productionmentioning
confidence: 99%
“…Root growth is controlled by endogenous constraints on carbon availability and environmental factors (Freschet et al 2017;McCormack et al 2015). Fineroot production is dependent on soil water content (Canham et al 2015) and the high plasticity of fine roots enables them to explore resource-rich soil patches has been demonstrated (Hodge 2004). The capacity of A. mangium and E. grandis roots to explore soil patches might therefore vary depending on the season and the depth in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Although strictly lignotuberous Banksia species are most likely to occur in the drier environments of SWA (Lamont and Markey ), lignotuber presence in adult B. attenuata plants is not correlated with long‐term average rainfall or maximum temperatures (Table ). The seedlings of lignotuberous species are less tolerant of drought than nonsprouters, possibly because early growth resources are used for lignotuber rather than rapid taproot growth that is critical for early survival (Enright and Lamont ; Canham et al ). Walters et al () reported that water and nutrient availabilities did not affect the lignotuber growth and resprouting ability of some eucalypt species.…”
Section: Discussionmentioning
confidence: 99%